2018
DOI: 10.1136/bcr-2017-222089
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of ectopic mediastinal parathyroid adenoma by 18F-fluorocholine PET/CT

Abstract: We report the case of two patients with newly diagnosed primary hyperparathyroidism: a 40-year-old woman during pregnancy and a 60-year-old man with initial hypercalcaemic crisis. In the first case, a bilateral neck exploration with parathyroidectomy during the second trimester of pregnancy was unsuccessful and the patient remained hypercalcaemic. Postpartum imaging assessment with technetium (Tc)-sestamibi scintigraphy could not supply conclusive diagnostic results. The use of F-fluorocholine (FCH) positron e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…A comparison is made between 99m Tc-sestamibi scintigraphy combined with single photon emission CT (SPECT)/CT and 18 F-fluorocholine PET/CT (FCH-PET/CT), revealing that FCH-PET/CT offers an equal or even superior detection of MPA [17]. 99m Tc-sestamibi parathyroid scan (SPS) with SPECT/CT were utilized in 53 patients with primary HPT, and revealed that SPS interpretation method correlated perfectly with the surgical finding in 48/53 patients (90.6%); it was on the correct side of the surgical finding but not the exact location in 3/53 (5.7%) and nonlocalizing in 2/53 (3.7%) [17]. SPS was utilized in localization of the MPA in our case with success, thus helping in the selection of the right surgical procedure (thoracotomy) to excise the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison is made between 99m Tc-sestamibi scintigraphy combined with single photon emission CT (SPECT)/CT and 18 F-fluorocholine PET/CT (FCH-PET/CT), revealing that FCH-PET/CT offers an equal or even superior detection of MPA [17]. 99m Tc-sestamibi parathyroid scan (SPS) with SPECT/CT were utilized in 53 patients with primary HPT, and revealed that SPS interpretation method correlated perfectly with the surgical finding in 48/53 patients (90.6%); it was on the correct side of the surgical finding but not the exact location in 3/53 (5.7%) and nonlocalizing in 2/53 (3.7%) [17]. SPS was utilized in localization of the MPA in our case with success, thus helping in the selection of the right surgical procedure (thoracotomy) to excise the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Such combination after failed neck exploration can ensure success of the second surgery [ 6 ]. 18F-fluorocholine PET/CT may localize EPA in pregnancy after negative/equivocal US and/or scintigraphy/single-photon emission computed tomography (SPECT) [ 24 ]. A multidisciplinary team can select the appropriate imaging with the least harm to both the mother and fetus [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In small studies of patients undergoing neck re-exploration, prevalence was 29–45% [ 1 ]. EPA can locate within the mediastinum as observed in Table 1 [ 6 , 12 , 15 , 16 , 24 ] or thymus [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary hyperparathyroidism (PHPT) is characterized by the autonomous secretion of parathyroid hormone (PTH) by one or more parathyroid glands. The most frequent cause of PHPT is a benign solitary parathyroid adenoma, which occurs in 80–90% of patients ( 1 , 2 ). An ectopic focus is demonstrated in up to 22% of the patients; the prevalence is even higher in the patients who undergo redo surgery ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…An ectopic focus is demonstrated in up to 22% of the patients; the prevalence is even higher in the patients who undergo redo surgery ( 3 , 4 ). Surgery is the only definitive cure for PHPT and is indicated in all symptomatic patients, as well as a defined subgroup of asymptomatic patients ( 2 , 5 ). The goals of parathyroid surgery are to remove all hyperfunctioning tissues and to preserve normal parathyroid tissues.…”
Section: Introductionmentioning
confidence: 99%